KETAATAN ANAK TERHADAP ORANG TUA DITINJAU DARI EFESUS 6:1-4 DALAM MENJAWAB FENOMENA PENINGKATAN KASUS ANAK MELAWAN ORANG TUA - Enny Irawati (STT BIBLIKA JAKARTA, 2021)
This study is intended to analyze deeply the understanding of children's obedience to their parents in terms of Ephesians 6: 1-4. This study used a qualitative research method, using literature study and inductive interpretation of the Bible based on analysis with three sub-(1) children's obedience, (2) respecting parents, (3) children willing to receive education. The results showed that children are obliged to respect their parents because it is God's command and there is a promise given to children who respect their parents. Parents have the authority to educate their children, therefore parents also have an obligation to educate their children from an early age in order to respect their parents. It can be concluded that cooperation between parents and children is needed. Between parents and children must be able to carry out their roles in accordance with their respective responsibilities that have been set out in the Word of God.